A single-phase bidirectional AC-AC converter with H-bridge energy buffer for wireless power transfer applications - Nazmul Hasan; Tarak Saha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper introduces a single-phase bidirectional AC-AC Matrix type converter for wireless power transfer (WPT) applications. The proposed converter converts mains 50 Hz alternating current (AC) directly to high frequency 85 kHz AC without an intermediate direct current (DC) conversion stage. A minimum cost realization of only two bidirectional AC switches comprised each of two semiconductor device and one gate drive signal is employed. The converter operation modes are quantum energy injection and circulating self-oscillation. Elimination of the DC link introduces a sag in the power transfer during the zero crossing of input AC mains, which is well documented in literature. A novel H-bridge buffer structure is introduced which eliminates the power sag by storing energy during mains peak and delivering energy during the zero-crossing period. The converter operates with inherent zero current switching, thus achieving a low switching loss and electro-magnetic interference. The control feature ensures that the converter can be used for both static and dynamic wireless charging applications. The bidirectional power transfer capability ensures that the system can operate in both grid to vehicle (G2V) and vehicle to grid (V2G) power transfer modes. The proposed converter design is analyzed analytically and verified through thorough simulation study.